Enterprise Intelligence based on Ontology Metadata - Guimarães, Francisco (2016)
Organizations define business models as part of its strategic thinking from which build performance evaluation structures focused on the effectiveness and efficiency of their goals. Usually the business model is captured in various organization representations with little interoperability between them. On the other hand, the performance are evaluated using business intelligence systems. Despite the usage of metadata in business intelligence and organization representation model system, metadata are normally not reused for the purpose of ensuring business concepts alignment. This article consolidates a vision of organizational metadata from various forms of representation of the business model, but implemented as ontology to support an organizational intelligence.